Queering and diversifying gender in equality work at European higher education institutions - Mense, Lisa; Sera, Stephanie; Vader, Sarah (My University, 2019)
Against the background of recent changes to EU legislation to meet the demands and needs of LGBTIQ* communities, the authors seek to situate a queered and diversified understanding of gender firmly at the centre of the gender equality discourse in higher education (HE). Based on case examples, the legal and discursive status quo in German and Dutch HE institutions as well as actors’ motivations, challenges and opportunities are examined through a queer lens. The results highlight how differently EU legislation is transposed into national law. They also show that change is currently driven by highly motivated individual actors, be they students, gender equality and diversity officers, or individual institutions. We argue that queering and diversifying should be understood and used as modes to reflect on and analyse the processes that lead to heteronormative understandings of gender in HE and to develop strategies that take the complexities of gendered identities and discrimination into account.
Keywords: EU political system; gender equality; Gleichberechtigung; higher education; non-discrimination; queer; ddc:370